The Influence of Work Environment and Workload On The Employee Performance of Surabaya Regional Health Laboratory With Work Motivation As An Intervening Variable - Irfan, Muhammad; Sukoco, Agus (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study aims to examine and analyze the influence of the work environment and workload on employee performance, with work motivation as an intervening variable. Design/methodology/approach: The research utilized a Saturated Sampling method, distributing questionnaires to all 44 employees of the Surabaya Regional Health Laboratory. Data were processed using the SEM-PLS application. Findings: The findings reveal that the work environment does not significantly affect employee performance, while workload has a significant impact on performance. The work environment significantly influences work motivation, as does workload. Moreover, work motivation significantly affects employee performance. However, neither the work environment nor workload has a significant effect on employee performance through work motivation as an intervening variable at the Surabaya Regional Health Laboratory. Originality/value: This study contributes to understanding the factors influencing employee performance at the Surabaya Regional Health Laboratory. It confirms that while workload directly impacts performance, the work environment, although positive, does not significantly enhance performance. Furthermore, work motivation plays a crucial role in directly boosting employee performance, though it does not serve as a significant intervening variable between the work environment or workload and performance. Paper type: Research paper